Multibeam bathymetry raw data (Atlas Hydrosweep DS 2 echo sounder entire dataset) of RV METEOR during cruise M53/3 - Monika Rhein (PANGAEA, 2023)
Multibeam bathymetry raw data using the ship extquotesingles own Atlas Hydrographic Hydrosweep DS 2 multibeam echo sounder was almost continuously recorded during RV METEOR cruise M53/3. Data was recorded on 28 days between 2002-06-07 and 2002-07-04. This dataset contains a survey in the Atlantic Ocean, covering an area east of the Brazilian coast and a survey towards the Caribbean Islands, followed by a survey between the Caribbean Islands. The approximate average depth of the entire dataset is around 4600m, however the depth varies from very shallow to deep water areas. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus no SVP files are added to this dataset. Data analysis of the multibeam raw could not reveal, whether the SVP has been changed during the survey. This publication is conducted within the efforts of the German Marine Research Alliance in the core area extquotesingleData management and Digitalization extquotesingle (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Note that refraction errors can be expected due to the lack of proper SVP. Overall, it appears that the data quality is rather bad to good since the gridded hillshade data showed occasionally relatively many obstacles, however also areas with less obstacles. The reason for the partially bad data quality is unknown. Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).